Active surveillance for prostate cancer: comparison between incidental tumors vs. tumors diagnosed at prostate biopsies - Luzzago, Stefano; Piccinelli, Mattia Luca; Marvaso, Giulia; Laukhtina, Ekaterina; Miura, Noriyoshi; Schuettfort, Victor M; Mori, Keiichiro; Aydh, Abdulmajeed; Ferro, Matteo; Mistretta, Francesco A; Fusco, Nicola; Petralia, Giuseppe; et al. (World journal of urology, 2022)
PURPOSE: To test discontinuation rates during Active Surveillance (AS) in patients diagnosed with incidental prostate cancers (IPCa) vs. tumors diagnosed at prostate biopsies (BxPCa). METHODS: Retrospective single center analysis of 961 vs. 121 BxPCa vs. IPCa patients (2008-2020). Kaplan-Meier plots and multivariable Cox regression models tested four different outcomes: (1) any-cause discontinuation; (2) discontinuation due to ISUP GG upgrading; (3) biopsy discontinuation due to ISUP GG upgrading or > 3 positive cores; (4) biopsy discontinuation or suspicious extraprostatic extension at surveillance mpMRI. Then, multivariable logistic regression models tested rates of clinically significant PCa (csPCa) (ISUP GG ≥ 3 or pT ≥ 3a or pN1) after radical prostatectomy (RP). RESULTS: Median time follow-up was 35 (19-64) months. IPCa patients were at lower risk of any-cause (3-year survival: 79.3 vs. 66%; HR: 0.5, p = 0.001) and biopsy/MRI AS discontinuation (3-year survival: 82.3 vs. 72.7%; HR: 0.5, p = 0.001), compared to BxPCa patients. Conversely, IPCa patients exhibited same rates of biopsy discontinuation and ISUP GG upgrading over time, relative to BxPCa. In multivariable logistic regression models, IPCa patients were associated with higher rates of csPCa at RP (OR: 1.4, p = 0.03), relative to their BxPCa counterparts. CONCLUSION: AS represents a safe management strategy for IPCa. Compared to BxPCa, IPCa patients are less prone to experience any-cause and biopsy/MRI AS discontinuation. However, the two mentioned groups present similar rates of biopsy discontinuation and ISUP GG upgrading over time. In consequence, tailored AS protocols with scheduled repeated surveillance biopsies should be offered to all newly diagnosed IPCa patients.
Keywords: Watchful Waiting; nádory prostaty; lidé; Biopsy; Prostate; retrospektivní studie; Humans; Prostatic Neoplasms; pozorné vyčkávání; Male; mužské pohlaví; Retrospective Studies; biopsie; prostata